2012
DOI: 10.1177/000313481207800618
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Violence: Implications for Resident Trauma Operative Experiences

Abstract: Trauma centers face novel challenges in resource allocation in an era of cost consciousness and work-hour restrictions. Studies have shown that time of day and day of week affect trauma admission volume; however, these studies were performed in cold climates. Data from 2000 to 2010 at a Level I trauma center were reviewed. Demographic, injury severity, and injury timing from 23,827 trauma patients were analyzed along with their emergency department disposition (operating room, intensive care unit, ward) and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…showed similar temporal variations in adult trauma at their single institution and suggested these finding may hinder general surgery residents' trauma experience, especially considering the current work hour restrictions. 13 Furthermore, adult trauma has been shown to occur more frequently with increasing temperature and during warm weather months of the year. 14,15 One study demonstrated that temperature is most highly predictive of increased trauma-related volume compared with other weatherrelated variables, such as rainfall, snowfall, and humidity.…”
mentioning
confidence: 99%
“…showed similar temporal variations in adult trauma at their single institution and suggested these finding may hinder general surgery residents' trauma experience, especially considering the current work hour restrictions. 13 Furthermore, adult trauma has been shown to occur more frequently with increasing temperature and during warm weather months of the year. 14,15 One study demonstrated that temperature is most highly predictive of increased trauma-related volume compared with other weatherrelated variables, such as rainfall, snowfall, and humidity.…”
mentioning
confidence: 99%
“…In line with other studies, we expect increased free time activity and so called disco journeys on Saturdays to be responsible for these results [ 22 , 26 ]. A younger patient age and an increased hospital admission during the night substantiate this theory [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 98%
“…The majority of the victims had faced the assault during the first half of the night. Violence-associated incidents are frequently reported at night, especially among men (17), and this is when people tend to consume alcohol while returning home after the day’s work (18). Victims’ own home is the location where the majority of these incidents had taken place.…”
Section: Discussionmentioning
confidence: 99%